PARASITES, PONDERAL INDEX AND LENGTH-WEIGHT RELATIONSHIP OF BARILIUS BENDELISIS (HAM.) AND PUNTIUS TICTO (HAM.) - Gatrola, Damayanti; Singh, Om Veer; Malhotra, Sandeep K; Nanda, Sunita; Ghildiyal, R P (Indian Journal of Fisheries, 2011)
This investigation includes report on the bionomics of economically important fishes, Barilius benddisis(Ham.) and Puntius liclo (Ham.) from diverse ecological situations. Peak values of Ponderal Index (K)in smaller (<8.0 cm) P. ticlo at Bakkas pond near Lucknow provide evidence of intensive feeding and rapidgrowth. Parabolic equations describing length-weight relationship in sex and size dasses of fishes aregiven